A Randomized, Placebo-Controlled Trial of the Quadrivalent Human Papillomavirus Vaccine in Human Immunodeficiency Virus-Infected Adults Aged 27 Years or Older: AIDS Clinical Trials Group Protocol A5298. (5th April 2018) - Wilkin, Timothy J; Chen, Huichao; Cespedes, Michelle S; Leon-Cruz, Jorge T; Godfrey, Catherine; Chiao, Elizabeth Y; Bastow, Barbara; Webster-Cyriaque, Jennifer; Feng, Qinghua; Dragavon, Joan; Coombs, Robert W; Presti, Rachel M; et al.
Abstract : Anal cancer is common in human immunodeficiency virus-infected adults. This randomized trial did not find a benefit from human papillomavirus (HPV) vaccination to prevent anal HPV infection or anal high-grade squamous intraepithelial lesions. There may be a benefit for prevention of oral HPV infections. Abstract: Background: Adults living with human immunodeficiency virus (HIV) are at increased risk for anal and oropharyngeal cancer caused by human papillomavirus (HPV). The efficacy of HPV vaccines in this population is unknown. Methods: In this phase 3, double-blind, randomized, controlled trial, we assigned HIV-infected adults aged ≥27 years to the quadrivalent HPV (types 6, 11, 16, 18) vaccine or placebo (1:1) stratified by sex and presence of anal high-grade squamous intraepithelial lesions on biopsy (bHSIL). The primary endpoint was vaccine efficacy against incident persistent anal infection with quadrivalent vaccine types or single detection at the final visit that were not present at baseline. Secondary endpoints included vaccine efficacy for anal bHSIL after week 52, persistent oral HPV infection. Results: A total of 575 participants were randomized. The Data and Safety Monitoring Board stopped the study early due to futility. Vaccine efficacy was 22% (95.1% confidence interval [CI], −31%, 53%) for prevention of persistent anal infection or single detection at the final visit, 0% (95% CI −44%, 31%) for improving bHSIL outcomes and 88% (95.1% CI 2%, 98%) for preventing persistent oral HPV infection, but was 32% (95.1% CI −80%, 74%) for 6-month persistent oral HPV infection or single detection at the final visit. Conclusions: These results do not support HPV vaccination of HIV-infected adults aged ≥27 years to prevent new anal HPV infections or to improve anal HSIL outcomes. However, our data suggest a role for prevention of oral HPV infections, but this finding should be confirmed in future studies. Clinical Trials Registration: NCT01461096.